Understanding the Binding Transition State After the Conformational Selection Step: The Second Half of the Molecular Recognition Process Between NS1 of the 1918 Influenza Virus and Host p85β - Dubrow, Alyssa; Kim, Iktae; Topo, Elias; Cho, Jae-Hyun (Frontiers in Molecular Biosciences, 2021)
Biomolecular recognition often involves conformational changes as a prerequisite for binding (i.e., conformational selection) or concurrently with binding (i.e., induced-fit). Recent advances in structural and kinetic approaches have enabled the detailed characterization of protein motions at atomic resolution. However, to fully understand the role of the conformational dynamics in molecular recognition, studies on the binding transition state are needed. Here, we investigate the binding transition state between nonstructural protein 1 (NS1) of the pandemic 1918 influenza A virus and the human p85 subunit of PI3K. 1918 NS1 binds to p85 via conformational selection. We present the free-energy mapping of the transition and bound states of the 1918 NS1:p85 interaction using linear free energy relationship and -value analyses. We find that the binding transition state of 1918 NS1 and p85 is structurally similar to the bound state with well-defined binding orientation and hydrophobic interactions. Our finding provides a detailed view of how protein motion contributes to the development of intermolecular interactions along the binding reaction coordinate.